HUKUM ISLAM DAN TRANSFORMASI SOSIAL MASYARAKAT JAHILIAH: STUDI HISTORIS TENTANG KARAKTER EGALITER HUKUM ISLAM - Muhammad Adib (MAQASHID Jurnal Hukum Islam, 2019)
The Prophet Muhammad SAW received a revelation from Allah SWT for the first time on Monday the 17th of Ramadan the 41st year of his birth, to coincide with the 6th August 610 AD Since that time, Muhammad bin Abdullah has carried out the mandate of nubuwwah from Allah SWT to bring Islam to the middle -human center, which turned out to be a teaching that overhauled the entire social system, especially the legal system that existed in the Jahiliyyah community. Islam comes to the midst of ignorant society by bringing a perfect syari'ah (legal system) so that it is able to regulate fair and egalitarian relations between human individuals in society. In principle, the emergence of the Prophet Muhammad by bringing egalitarian teachings, can be considered as a social change to the truth that is happening in society, especially the legal system, with revelation and guidance from Allah SWT.